Returns to Talent and the Finance Wage Premium - Célérier, Claire; Vallée, Boris (Review of Financial Studies, 2019)
To study the role of talent in finance workers’ pay, we exploit a special feature of the French higher education system. Wage returns to talent have been significantly higher and have risen faster since the 1980s in finance than in other sectors. Both wage returns to project size and the elasticity of project size to talent are also higher in this industry. Last, the share of performance pay varies more for talent in finance. These findings are supportive of finance wages reflecting the competitive assignment of talent in an industry that exhibits a high complementarity between talent and scale. Received October 11, 2017; editorial decision September 4, 2018 by Editor Stijn Van Nieuwerburgh. Authors have furnished an Internet Appendix, which is available on the Oxford University Press Web site next to the link to the final published paper online.